Aerodynamic load analyses of less-emission HTS maglev train in evacuated tube transport system - Wang, Xuanbo; Zheng, Jun; Rao, Yingyu; Zhang, Yong; Deng, Zigang; Hu, Xiao (Frontiers in Energy Research, 2023)
An evacuated tube transport (ETT) system is proposed by combining evacuated tube technology and high temperature superconducting (HTS) maglev technology in this paper. It can be predicted that this future transport mode can own the advantages of less emission, low noise, high efficiency, and convenience, suitable for high-speed or super-high-speed application. The train running at a high speed will inevitably cause complex aerodynamic load behaviors in an enclosed low-pressure tube, which further affects the real energy consumption and the fatigue life of the components. In order to explore how the aerodynamic load behaves in an ETT-HTS Maglev system, we established a three-dimension numerical calculation model based on ANSYS FLUENT software. The steady aerodynamic loads on the train’s surface and the tube’s inner surface are investigated under different pressures and different operation speeds. It is found that the aerodynamic load on the surface of the train and tube is significantly affected by the pressure inside the tube and the running speed of the train. The aerodynamic load fluctuations at the rear of the train are relatively more violent than those at the head. We also found that the impact of compression wave and expansion wave on aerodynamic loads at different positions of the tube is related to the size of the flow field space between the tube and the train. These results can provide some reference for the less-emission train body design and the whole ETT-HTS Maglev system structural strength in the near future.